Schizosaccharomyces pombe Pak-related protein, Pak1p/Orb2p, phosphorylates myosin regulatory light chain to inhibit cytokinesis - Loo, Tsui-Han (The Rockefeller University Press, 2008)
p21-activated kinases (Paks) have been identified in a variety of eukaryotic cells as key effectors of the Cdc42 family of guanosine triphosphatases. Pak kinases play important roles in regulating the filamentous actin cytoskeleton. In this study, we describe a function for the Schizosaccharomyces pombe Pak-related protein Pak1p/Orb2p in cytokinesis. Pak1p localizes to the actomyosin ring during mitosis and cytokinesis. Loss of Pak1p function leads to accelerated cytokinesis. Pak1p mediates phosphorylation of myosin II regulatory light chain Rlc1p at serine residues 35 and 36 in vivo. Interestingly, loss of Pak1p function or substitution of serine 35 and serine 36 of Rlc1p with alanines, thereby mimicking a dephosphorylated state of Rlc1p, leads to defective coordination of mitosis and cytokinesis. This study reveals a new mechanism involving Pak1p kinase that helps ensure the fidelity of cytokinesis.